Designing a Welfare-Oriented Human Resource Management Model - Bijhan Nasiri; Hamid Zare; Mohammad Reza Jaber Ansari (مدیریت بهره وری)
Considering the importance of the subject, the present research is an attempt to design a welfare-oriented human resource management model. The method is a qualitative study that was conducted using in-depth interviews. The participants were expert faculty members, management specialists and those involved in the design of welfare-oriented human resources management model in 1400-1401. Sampling in the qualitative section was done purposefully using the expert network technique, in which 15 people participated in the interview. The final results of the research based on the interviews showed that the factors affecting welfare-oriented human resource management are: 1)causal factors (participatory management, employee motivation, attention to employee needs, employee relations, training, meritocracy, welfare services, and empowerment); 2)contextual factors (laws and regulations, organizational culture, organizational structure and economic factors); 3)intervention factors (strict laws and regulations, salaries and wages, injustice, lack of attention to education; traditional management styles; lack of paying attention to expertise; and not paying attention to motivational issues), and 4)strategies (planning, facilities and equipment and financial resources), the components of welfare-oriented human resource management (satisfaction with the work environment, health and safety, performance management, use of employee opinions, employee development); and consequences (productivity, profitability, improvement of organizational commitment, acceptance of change, and excellence of the organization). Based on the findings of this research, it can be said that there are many causal, interventional, contextual factors and strategies that have an effect on welfare-oriented human resource management, which should be paid attention to.